Pengembangan Media Pembelajaran Berbasis Augmented Reality (AR) Pada Materi Siklus Hidup Hewan Di Kelas III - Yuliskha Putri; Lidia Simanihuruk; Fahrur Rozi; Try Wahyu Purnomo; Suyit Ratno (Jurnal Keluarga Sehat Sejahtera, 2026)
This study aims to determine the validity, practicality, and effectiveness of Augmented Reality (AR)-based learning media on the topic of the animal life cycle for Grade III students of SD Negeri 060954 Medan. The research method used in this study was Research and Development (R&D) with the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The research subjects consisted of a material expert, a media expert, a teacher, and 23 students of class III C at SD Negeri 060954 Medan. The data collection techniques used in this study were observation, interviews, questionnaires, and tests. The results of the study show that: (1) the Augmented Reality-based learning media developed obtained a validation percentage of 94% from the material expert and 97% from the media expert, both of which fall into the “Very Valid/Feasible” category; (2) the practicality test results based on teacher responses obtained a percentage of 95% and student responses obtained 94%, which are categorized as “Very Practical”; and (3) the effectiveness test results based on students’ pretest and posttest scores obtained an N-gain score of 0.6783 with a percentage of 67.83%, which falls into the “Moderately Effective” category. Therefore, the Augmented Reality-based learning media on the animal life cycle material is declared very valid, very practical, and moderately effective for use in the learning process.